Efficacy and safety of NeoAdjuvant chemotherapy with or without tIslelizumab followed by debulking surgery for oVarian cancEr (NAIVE study) in China: study protocol of an open-label, phase II, randomised controlled trial - Ying Zhu; Jianwei Zhou; Zhigang Zhang; Jiaojiao Zhang; Jing Fei; Xiaoqing Zhu (BMJ Open)
Introduction The prognosis for epithelial ovarian cancer (EOC) is exceedingly poor, with patients diagnosed with stage III/IV tumours typically offered cytoreductive surgery in conjunction with chemotherapy as a standard treatment option. This approach is intended to reduce the risk of surgery and address ovarian cancers that are not amenable to surgical intervention. A promising alternative and important treatment option is neoadjuvant chemotherapy (NACT) in conjunction with interstitial tumour cytoreductive surgery. The combination of neoadjuvant immunotherapy with chemotherapy has recently demonstrated remarkable efficacy, particularly in melanoma and lung cancer, with notable pathological responses and therapeutic benefits in tumour tissue. The NeoAdjuvant chemotherapy with or without tIslelizumab followed by debulking surgery for oVarian cancEr(NAIVE) study aims to assess the clinical efficacy and safety of NACT in combination with tislelizumab (a monoclonal antibody for programmed cell death protein 1) for advanced EOC.Methods and analysis The NAIVE study is an investigator-initiated, prospective, single-centre, open-label, randomised controlled trial for advanced EOC with the International Federation of Gynaecology and Obstetrics (FIGO) stage IIIc with a Suidan CT score of 3 or greater or a Fagotti laparoscopic score of 8 or greater; or FIGO stage IV. The primary endpoint of the study is the 1-year progression-free survival (PFS) rate, measured as the percentage of patients who are free of tumour progression or death for 1 year after receiving the first dose of study drug. The secondary endpoints encompassed the R0 resection rate, the clinical response rate and other relevant metrics. Enrolled patients will be randomly assigned in a 1:1 ratio to either the experimental arm, which will receive neoadjuvant platinum-based chemotherapy in combination with tislelizumab, or the control arm, which will receive neoadjuvant platinum-based chemotherapy. The study will enrol 40 patients, with enrolment scheduled to start in April 2021 and complete in April 2025, given a 1-year PFS rate of 60%. The study will provide new evidence regarding the clinical efficacy and safety of NACT in combination with tislelizumab for advanced ovarian cancer. The results will contribute to a deeper understanding of the clinical effects, safety profile and fundamental immunological processes. The findings will contribute to the growing body of evidence in support of the incorporation of immunotherapy into the treatment paradigm for ovarian cancer, thus facilitating the development of more personalised and efficacious therapeutic modalities.Ethics and dissemination This trial has received ethical approval from the Institutional Ethics Committee of the Second Affiliated Hospital of the Medical College of Zhejiang University. Presentations at scientific and professional meetings and publication in peer-reviewed journals will disseminate the results of the study.Trial registration number NCT04815408.